Nitrogen, sulfur and oxygen donor adducts with copper(II) complexes of antitumor 2-formylpyridinethiosemicarbazone analogs: Physicochemical and cytotoxic studies - Ainscough, E.W. (2014)
10.1016/S0162-0134(98)10011-9